2019
DOI: 10.1021/acs.jafc.9b04178
|View full text |Cite
|
Sign up to set email alerts
|

Ginkgolic Acids Impair Mitochondrial Function by Decreasing Mitochondrial Biogenesis and Promoting FUNDC1-Dependent Mitophagy

Abstract: Ginkgolic acids (GAs) are found in the leaves, nuts, and testa of Ginkgo biloba and have been reported to exhibit antitumor, antibacterial, and pro-apoptotic activities. However, their role in mitochondrial function is still unclear. Our previous study showed that genes related to the mitochondria present significant changes in GA-treated mouse bone marrow stromal cells. We hypothesize that GAs may regulate mitochondrial function. Here, we found that GA treatment induced mitochondrial fragmentation, reduced mt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 70 publications
0
14
0
Order By: Relevance
“…The vast majority of available data comes from preclinical studies. Natural compounds, such as pomegranate and Ginkgo biloba extracts, or chemical compounds modulators of mitophagy have been tested mainly in vitro [ 412 , 413 , 414 ]. A new type of molecule initially developed for cancer treatment is attracting significant scientific interest as a promising mitophagy therapeutical tool, the so-called selective, ubiquitin-mediated “autophagy targeting chimera” (AUTAC) [ 415 ], which is able to potentiate mitochondrial turnover and facilitate the removal fragmented mitochondria in vitro in fibroblasts [ 416 ].…”
Section: Targeting Mitophagymentioning
confidence: 99%
“…The vast majority of available data comes from preclinical studies. Natural compounds, such as pomegranate and Ginkgo biloba extracts, or chemical compounds modulators of mitophagy have been tested mainly in vitro [ 412 , 413 , 414 ]. A new type of molecule initially developed for cancer treatment is attracting significant scientific interest as a promising mitophagy therapeutical tool, the so-called selective, ubiquitin-mediated “autophagy targeting chimera” (AUTAC) [ 415 ], which is able to potentiate mitochondrial turnover and facilitate the removal fragmented mitochondria in vitro in fibroblasts [ 416 ].…”
Section: Targeting Mitophagymentioning
confidence: 99%
“…Like ancient Chinese philosophy “Ying” and “Yang,” both generation of newly synthesized mitochondria, by mitochondrial biogenesis, and elimination of detrimental and/or superfluous mitochondria, by mitophagy, are predominantly required for maintaining mitochondrial homeostasis. Recent findings have hinted that any abnormality in these two opposing processes can influence the quantity and quality of mitochondria, which will further affect mitochondrial function and the ability of cells to adjust their mitochondrial networks in response to physiological adaptations and stress conditions ( Palikaras et al, 2015 ; Singh et al, 2018 ; Wang et al, 2019 ; Yau et al, 2019 ; Zhou et al, 2019 ; Chen et al, 2020 ). At the same time, impaired mitochondrial function and homeostasis are now widely accepted to be associated with multiple aspects of the aging process and age-onset diseases ( Lopez-Otin et al, 2013 ; Mattson and Arumugam, 2018 ; Akbari et al, 2019 ).…”
Section: A Balanced Act Of Mitochondrial Biogenesis and Mitophagymentioning
confidence: 99%
“…FUNDC1 is localized on the outer mitochondrial membrane and participates in mitochondrial autophagy caused by hypoxia and reduced mitochondrial membrane potential, in which the phosphorylated form of FUNDC1 inhibits autophagy while dephosphorylation promotes autophagy [20,21]. Wang et al found that mitochondrial DNA copy number and mitochondrial protein expression were signi cantly decreased in Ginkgolic acids-treated mouse bone marrow stromal cells, but FUNDC1 gene knockout restored Ginkgolic acids-induced changes in mitochondrial mass loss and mitochondrial membrane potential loss [22]. Another study showed that FUNDC1 plays an important regulatory role in hypoxia-induced PC12 neuroautophagy and apoptosis, and overexpression of FUNDC1 can promote autophagy and then prevent neuronal apoptosis [20].…”
Section: Discussionmentioning
confidence: 99%